Asymptotic Representations for Solutions of One Class of Systems of Quasilinear Differential Equations - Evtukhov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish asymptotic representations for solutions of one class of systems of differential equations appearing in the investigation of the asymptotic behavior of nth-order quasilinear differential equations.